Proposed Grading System at Academia Dele Carre Inc. (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
This paper presents a grading system that was developed to collect the information of the students’ records in Academia De Le Carre Inc. The grading system is designed to provide incentives for achievement and assist in identifying problem areas of students. Students can interactively use program assignments. The Grade is automatically recorded. This paper also considers the security problem with an automatic grading system. In considering the specifications of systems used to award grades for student achievement, the researchers planned a strategic way for the benefits of Academia De Le Carre Inc. First, they gathered the information and interviewed Ma’am Cherry Rose C. Maza at Academia De Le Carre. The researchers gathered information by using a questionnaire and analyzed what will be the output of documentations and the system. After all the planning and analysis were done, the system design will take place. The researcher will make sure the overall design and user interface (UI) as prescribed by the end-user are met. The primary purpose of testing is to detect software failure to discover and correct defects. A grading system is developed to compute the grades of the student. Programming language is used to develop the interface During this phase, the system will be installed in the Academia Dele Carre. During the maintenance phase, errors or defects, which would require repairs, may exist. The researchers develop the following deliverables to create a grading system: (1) login page, which is only for the user of the school to secure all the data collected in the grading system; (2) registration page, which is for the students who want to register in the login form; (3) record page, which contains the database of the students (only the teacher can see all records and edit the grades); (4) the only administrator can see the record of the user. The existing grading system is more different than a computerized grading system. The existing grading system is time-consuming, while a computerized grading system will create an easier and convenient way of computing the grades of the students by recording all the information and grades. The computerized system only focuses on the average grades of the students. This system will allow searching for all the grades needed at a time easily.
Keywords: grading system